2011
DOI: 10.1016/j.ctim.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of Complementary and Alternative Medicine in pregnancy: Data from the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: word count: 297 Main text word count: 2999Page 2 of 16 ObjectivesTo report the frequency of Complementary and Alternative Medicine (CAM) use by a population of pregnant women in the UK. DesignFour postal self-completion questionnaires completed at 8, 12, 18 and 32 weeks' gestation provided the source of CAMs used. Questions asked for written descriptions about the use of any treatments, pills, medicines, ointments, homeopathic medicines, herbal medicines, supplements, drinks and herbal teas. SettingAn observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 45 publications
2
62
1
4
Order By: Relevance
“…Previous studies have investigated the effects of acupuncture (Betts et al, 2012;Borup et al, 2009), homeopathy (Hochstrasser and Mattmann, 1994), Ayurveda (Jayashree, 2008), yoga (Narendran et al, 2005b;Rakhshani et al, 2010), and Qigong (Zhou and Lian, 1989) during pregnancy (Bishop et al, 2011;Kalder et al, 2011;Steel and Adams, 2011). Such interventions have been shown to be effective in reducing occurrences of hypertensive disorders of pregnancy (Hofmeyr et al, 2010;Zhou and Lian, 1989), preventing preterm deliveries (Hochstrasser and Mattmann, 1994;Imdad et al, 2011;Sibai, 2011), improving fetal outcomes (Hochstrasser and Mattmann, 1994;Sabour et al, 2006), and enhance quality of life (Rakhshani, 2013;Rakhshani et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have investigated the effects of acupuncture (Betts et al, 2012;Borup et al, 2009), homeopathy (Hochstrasser and Mattmann, 1994), Ayurveda (Jayashree, 2008), yoga (Narendran et al, 2005b;Rakhshani et al, 2010), and Qigong (Zhou and Lian, 1989) during pregnancy (Bishop et al, 2011;Kalder et al, 2011;Steel and Adams, 2011). Such interventions have been shown to be effective in reducing occurrences of hypertensive disorders of pregnancy (Hofmeyr et al, 2010;Zhou and Lian, 1989), preventing preterm deliveries (Hochstrasser and Mattmann, 1994;Imdad et al, 2011;Sibai, 2011), improving fetal outcomes (Hochstrasser and Mattmann, 1994;Sabour et al, 2006), and enhance quality of life (Rakhshani, 2013;Rakhshani et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…It used to treat dysmenorrhea and delayed menses (Flores & Quinlan 2014). Clinical studies showed that Matricaria aurea (Chamomile) is used for nausea and vomiting intervention in early pregnancy (Bishop et al 2011;Matthews et al 2014) or throughout pregnancy (Broussard et al 2010;Holst et al 2011). A higher incidence of threatening miscarriages and preterm labors was observed among regular pregnant users of chamomile (Cuzzolin et al 2010).…”
Section: Herbal Remedies Of Fertility Pregnancy-related Issues and mentioning
confidence: 99%
“…Flavonoids, tannins and sesquiterpenes (-bisabolol and farnesene) (Minaiyan et al 2010;Aboul et al 2012;Afifi & Kasabri 2014); coumarins, phenolic compounds, polyacetylenes, flavones, flavonols and flavonones Aboul et al 2012); Essential oil (monoterpenes), triterpenes and fatty acids (Capuzzo et al 2014). Chamomile is used as anti-nausea and antiemtic in early pregnancy (Bishop et al 2011;Matthews et al 2014) or throughout pregnancy (Broussard et al 2010;Holst et al 2011). A higher incidence of threatening miscarriages and preterm labors was observed among regular pregnant users of chamomile (Cuzzolin et al 2010).…”
Section: Herbal Remedies With Female Antifertility and Abortificiant mentioning
confidence: 99%
“…3,5 Numerous large scale surveys have identified CAM as increasing in popularity in North America, Australia and Europe 7,10,16,28 and such trends have generated much interest among health professionals and policy-makers. 21,34 Previous research has consistently identified women as core consumers of CAM 2,13,19 and findings indicate that the use of CAM is common with regards to a number of women's health issues including pregnancy, 4,20,26 menopause, 15,40 breast cancer 32 and depression. 12,43 In Australia, research has identified CAM use as substantial for both young (aged 18-23) and mid-age (aged 45-50) women.…”
Section: Introductionmentioning
confidence: 98%